On the quantum phase fluctuations of coherent light coupled to a degenerate parametric amplifier - Alam, Mohosin; Mandal, Swapan; Wahiddin, Mohamed Ridza (Elsevier, 2016)
The solutions of the field operators of a degenerate parametric amplifier under rotating wave approximation are used to investigate the quantum phase fluctuation of input coherent light. In the present investigation, we use the phase fluctuations parameters U, S and Q due to Carruthers and Nieto. On the other hand, the sine and cosine of the phase operators are evaluated under Barnett-Pegg formalism. The complete analytical expression for the phase fluctuation parameters of the input coherent light is expressed as functions of interaction time, phases and photon numbers of input coherent light. In order to provide the physical realization of the phase fluctuation parameters, we give few numerical estimates closed to the experimental situation. We establish that for the phase fluctuation parameters are extremely sensitive to the incident coherent light. We report the reduction and enhancement of the phase fluctuation parameters compared to their initial values.